Dissociation between muscle metabolism and oxygen kinetics during recovery from exercise in patients with chronic heart failure - Hanada, A (2000)
OBJECTIVE—To estimate muscle metabolism and oxygen delivery to skeletal muscle in patients with chronic heart failure. METHODS—13 patients with chronic heart failure and 15 controls performed calf plantar flexion for six minutes at a constant workload of 50% of one repetition maximum. During recovery from exercise, skeletal muscle content of oxygenated haemoglobin (oxy-Hb) and the level of phosphocreatine (PCr) were measured by near-infrared spectroscopy and (31)P-magnetic resonance spectroscopy, respectively. RESULTS—The mean (SD) time constants of PCr and oxy-Hb during recovery from exercise were significantly greater in patients with chronic heart failure than in normal subjects (τ PCr: 76.3 (30.2) s v 36.5 (5.8) s; τ oxy-Hb: 48.3 (7.3) s v 30.1 (7.7) s; p < 0.01). Both time constants were similar in normal subjects, while the τ PCr was significantly greater than the τ oxy-Hb in patients with chronic heart failure. CONCLUSIONS—The slower recovery of PCr compared with oxy-Hb in patients with chronic heart failure indicates that haemoglobin resaturation is not a major rate limiting factor of PCr resynthesis. It is suggested that muscle metabolic recovery may depend more on oxygen utilisation than on haemoglobin resaturation or oxygen delivery in patients with chronic heart failure.   Keywords: near-infrared spectroscopy; (31)P-magnetic resonance spectroscopy; chronic heart failure; exercise tolerance